A facile method to prepare g-carbon nitride/poly(vinyl alcohol) nanocomposite films with remarkable optoelectrical properties: Laser attenuation approach. (February 2021) - Ismail, A.M.; Mohammed, M.I.; Yahia, I.S.
Highlights: A new designed optical system based on g-carbon nitride doped poly(vinyl alcohol) prepared successfully. X-ray diffraction (XRD) illustrates a uniform and semicrystalline structure in nature for the obtained samples. Both direct and indirect bandgaps were calculated and analyzed. The studied polymeric composites films are highly attenuated for the laser beam of 632.8 nm. The designed g-C3 N4 /PVA composites can be extensively appropriate to the optoelectronic applications. Abstract: Nanocomposites consisting of polyvinyl alcohol (PVA) and graphitic carbon nitride nanoparticles (g-C3 N4 ) were fabricated by solution casting technique. XRD has shown that the semicrystalline PVA structure is greatly affected by the incorporation of g-C3 N4, which is confirmed by SEM images. Optical characteristics are investigated at room temperature within the wavelength range (200–1500 nm). The effect of g-C3 N4 content on the optical band gap was studied. The optical bandgaps, direct and indirect, of g-C3 N4 doped films, is lower than pristine PVA. Urbach's energy increased from 0.42 eV for PVA to 0.96 eV for 14.8 wt% g-C3 N4 doped film. The dielectric constant ε ′, dielectric loss ε ″, and AC electrical conductivity σ ac at RT as a function of frequency from 100 Hz to 1 MHz, and g-C3 N4 doping level were studied. The variation of σ ac with frequency was analyzed in view of Jonscher's universal power law. Adding g-C3 N4 appears to enhance the σ ac of the films to higher values that candidates them in semiconductors applications. The results optical limiting indicates that the samples doped with g-C3 N4 are highly attenuated for the laser beam of 638.2 nm. g-C3 N4 -doped PVA is a promising candidate for electronic and optoelectronic applications, especially the attenuation of laser power.